Ligações de hidrogênio intramoleculares: um estudo teórico de compostos di-carbonílicos - Bezerra, Aline Fonseca (2009)
The intramolecular hydrogen bond occurs when the same molecules has both proton donor and proton acceptor groups in satisfactory configuration space for the formation of this interaction. It is important to note the changes in the structural, electronic and vibrational properties that occur due to the formation of this interaction. In the hydrogen bonding formation is an important phenomenon called charge transfer , where part of the electronic density of the proton acceptor species, Y, is transferred o the proton donor specie, HX. With respect to the vibrational spectrum are observed changes in the way of straightening of donor and acceptor proton species. Di-carbonyl compounds (C3H2O2R2) with their substituent groups (R=CH3, CN, H, NH2, OH and SH) were studied focusing on the energetic, structural, vibrational and electron density analysis. Initially the energy and structural analysis were carried out starting from the molecules optimized geometry. We also evaluated of the strength s hydrogen bonding and the length s intramolecular bond. The QTAIM study was performed to obtain the electron density s values and the electron density s Laplacian values and verify the existence of the bond critical point in the intramolecular hydrogen bond. From the harmonic vibrational spectra was possible to identify changes in the vibrational modes, related the intramolecular interaction s formation.